Effect of cigarette smoking, pulmonary inflammation, and lung disease on concentrations of carcinoembryonic antigen in serum and secretions. Issue 1 (January 1986) - Stockley, R A; Shaw, J; Whitfield, A G; Whitehead, T P; Clarke, C A; Burnett, D
Abstract : A specific radioimmunoassay for carcinoembryonic antigen was used to investigate aspects of its measurement in lung disease. The results confirm that serum carcinoembryonic antigen concentrations are higher in healthy smokers and patients with chronic obstructive bronchitis than in healthy non smokers (p less than 0.01). Corticosteroid treatment reduced the concentration in nine patients with bronchitis (p less than 0.05). Other inflammatory lung diseases (bronchiectasis, pneumonia, fibrosing alveolitis) are not associated with a raised serum carcinoembryonic antigen concentration. The sputum concentrations were about 100 times those found in serum and there was a positive correlation (r = 0.611 2p less than 0.01) between the concentrations in sputum and serum in patients with bronchitis. No preferential rise in sputum concentration was found in current smokers or patients with lung carcinoma (n = 16). A higher ratio of carcinoembryonic antigen to albumin concentration (p less than 0.05) was, however, found in lavage fluid obtained from the tumour site than in fluid from "normal" lung in the same patients, suggesting an increase in carcinoembryonic antigen secretion in the vicinity of the tumour. Despite this "local" effect the sputum concentration does not, however, appear to be a useful marker of lung carcinoma and the measurement could not be used as a screening test.